Peningkatan Peluang Bisnis Strategis Pada Pemasangan SPM dan Jalur Pipa Bawah Laut Proyek Supply Avtur ke Bandara Soekarno Hatta Dari Refinery Unit VI Balongan - Edy Soesanto Edy (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
Increasing business opportunities from an economic aspect that includes the financial performance of the Refinery Unit VI is very important to manage. Good financial performance will support the company's business continuity, and also have a positive impact on stakeholders. Refinery Unit VI's commitment to improving financial performance is very high, and strives to achieve predetermined key performance indicators (KPI). Refinery Unit VI measures the achievement of KPI regularly every quarter as part of the evaluation. Targets related to current economic performance are the achievement of KPIs on Refinery Gross Margin and Net Margin. The person in charge for recording and reporting financial performance is under the Financial Function. Refinery Unit VI uses Internal Control over Financial Reporting (ICoFR) to control financial reports, where each function that has the authorization uploads it on the ICoFR web system. In 2017, Refinery Unit VI succeeded in 100% compliance with the IcoFR. The realization of the Refinery Unit VI financial performance from 2015 was always above the target despite fluctuations in product prices. This is a good thing, supported by the achievement of the increasing Gross Refinery Margin and Net Margin from 2015–2017. Refinery Unit VI has continuously succeeded in improving financial performance and achieving the highest Gross Refinery Margin among all Refinery Units owned by PT Pertamina (Persero). The installation of SPM and subsea pipelines is the target of increasing the Refinery Unit VI development program.